VALIDATION OF THE METHOD FOR DETERMINING THE AMOUNT OF Na+ AND K+ IONS IN THE COMBINED DRUG «REHYDRATE ZINC» AND EVALUATION OF THE STABILITY OF THE STABILITY OF THE METHOD - Kholturaeva Gulnoza Mirkamilovna; Ganieva Hilola Gayratovna; Ubaydullaev Kudratilla Asadullaevich (Western European Studies, 2024)
In this study, the purity and amount of sodium (Na+ ) and potassium (K+ ) ions contained in the drug "Rehydrate Zinc" were determined using atomic absorption flame spectrometric methods (in the emission mode). The advantages of the combined use of atomic absorption and atomic emission spectrometric methods, the exclusion of destructive factors in the analysis of substances contained in complex drugs, the correct choice of a nebulizer and temperature, as well as the stability of the method when using highly sensitive methods were studied. The developed method of analytical analysis was validated for the following parameters: specificity, linearity, precision and reliability. The emission and atomic absorption flame spectrometric method can be used in manufacturing plants and research laboratories, in quality control and standardization of rehydrating solutions containing electrolytes, infusion solutions
Keywords: atomic absorption spectrometry; Shewhart control charts; precision